Digital Storytelling in TEYL: A Narrative Inquiry of a Pre-Service Teacher - Wisnumurti, Paulus Krisna; Setyaningsih, Endang; Wahyuni, Dewi Sri (JOLLT Journal of Languages and Language Teaching, 2021)
Digital storytelling is a relatively fast-growing currency in many classrooms, particularly in the context of TEYL. In the past decade, numerous studies have captured this trend as listed in the major research databases. Regardless of the rich documentation, it is rare to find an investigation on the area from the perspective of narrative inquiry. This study attempts to fill the methodological gap and seeks to answer two research questions: (1) How does the implementation of digital storytelling in Teaching English to Young Learners (TEYL)? (2) How do the students respond to the use of digital storytelling? Conducted in an elementary school in Surakarta, this study depicts the story of a pre-service teacher when he used digital storytelling to teach English to fifth graders of an elementary school in Surakarta, Indonesia. The data of this study were obtained through video recording, field notes, and students’ reflection. The study reveals that digital storytelling can be delivered through various models and is open to combinations of technology. One model applied in this study has the following general steps: an opening, focusing on the story, further exercises, and closing. Activity which including the interaction between the teacher and students such as QnA observably preferred by the students.